Renal infarction due to polyarteritis nodosa in a patient with angioimmunoblastic T-cell lymphoma: a case report and a brief review of the literature - Ambrosio Maria; Rocca Bruno; Ginori Alessandro; Onorati Monica; Fabbri Alberto; Carmellini Mario; Lazzi Stefano; Tripodi Sergio (BMC, 2012)
Abstract Angioimmunoblastic T-cell lymphoma is one of the most common subtypes of peripheral T-cell lymphoma (15-20% of all cases), accounting for approximately 1-2% of all non-Hodgkin lymphomas. It often presents autoimmune phenomena including hemolytic anemia, thrombocytopenia, glomerulonephrities and circulating immune complexes. Polyarteritis nodosa is an autoimmune disease characterized by necrotizing vasculitis of medium vessels, which rarely develops in association with hematological malignant disorders. Herein we report the case of a 40-year-old man who underwent lymph node biopsy in the suspicious of sarcoidosis. On the basis of histological and immunohistochemical findings, the diagnosis of angioimmunoblastic T-cell lymphoma was performed. The patient was successfully treated with cytarabine-based regimen for 6 cycles. Three months after the initial diagnosis of angioimmunoblastic T-cell lymphoma, a whole body computed tomography showed a lesion in the lower pole of the left kidney. Renal cell carcinoma was suspected, thus a nephrectomy was carried out. The histological findings were compatible with polyarteritis nodosa. To the best of our knowledge, the association between polyarteritis nodosa and angioimmunoblastic T-cell lymphoma has been described only once. This relation may be secondary to the induction of an autoimmune phenomenon by the lymphoma with the formation of circulating immune complexes, leading to vessels walls injury. A careful evaluation is needed in the management of angioimmunoblastic T-cell lymphoma patients with signs of renal failure in order to avoid delay of treatment and organ damage.